ANALYSIS OF DYNAMIC CHARACTERISTICS OF THE HIGH-SPEED GEAR SHAFT SYSTEM - ZHOU HongKai; ZHANG LiYong; QIAO XueTao; HU CaoDi; HUANG ShouFeng; WEI LeYu (Jixie qiangdu)
The inherent characteristics of the high speed shaft and the unbalance response of the high speed shaft seriously affect the operating condition and service life of the high speed gearbox. For the high speed gear shaft,a multi distribution model of the system is established. The natural frequency and the unbalance response of the shaft are analyzed by using the transfer matrix method. The unbalance response of the shaft at different speeds and different eccentric quality is obtained with the same method. The unbalance response of the gear meshing point is investigated through the analysis of the unbalanced response characteristics in various cases,and the working conditions of the gear meshing point are analyzed,and the basis for the design and manufacture of high speed gear box is provided.